The Virtue of Morality: A Comparative Study Between Indonesia and England - Zakki Adlhiyati; Harjono Harjono (Universitas Negeri Semarang, 2023)
This article examines the morality of tort in Indonesian and English civil law. This is legal research by studying statutory regulations, court decisions and other related documents. A tort is an act that can harm another party. Based on the results and discussion, it is known that the concept of morality is found in the broader meaning of tort in Indonesia. Similar to Indonesia, England also aligns the concept of unlawful acts with morality. This can be seen in the neighbour principle, which then gives rise to the duty of care. Through this principle, a person must be careful, especially towards people in direct contact with us, so that our actions, whether active or passive, do not cause harm to other people. Morality, whether in Indonesia or England, is one of the keys to determining whether an action is against the law. In the Donoghue v. Stevenson case, reason is used to apply morality; conversely, in tort law in Indonesia, judges are expected to use divine values and reason in applying morality.